Characteristics and treatment modes of industrial wastewater in new energy vehicles industrial park - LI Dian; WANG Xun; LIU Yingming (Gongye shui chuli)
New energy vehicles have become the representative of “new quality productivity” in China. The wastewater quality characteristics, the quantity index, treatment modes, and key pollutants treatment methods of the new energy vehicle industry were summarized. The pollutants of new energy vehicles wastewater was complex, toxic and difficult to be directly biodegraded. The wastewater mainly contained pollutants such as surfactants, mineral oil, phosphate and heavy metal. By reviewing the environmental impact assessment reports of 21 key enterprises in the industry, it was found that the wastewater from the new energy vehicle industry was mainly generated by enterprises such as vehicle manufacturing and energy storage device manufacturing. From the policy perspective, when the new energy vehicle industry formed agglomeration and scale effects, it was necessary to build supporting wastewater treatment plants in new energy industrial parks. The characteristic pollutants such as heavy metal ions and surfactants in wastewater needed to be given special consideration in the pretreatment stage to improve the biodegradability of wastewater. It was recommended to apply new technologies to actual new energy industry wastewater treatment work as soon as possible, and to increase the research and development of environmentally friendly surfactants. Each region needed to conduct water quality and quantity analysis in advance based on the current situation and development plans of the park, and dispose key pollutants in a targeted manner. At the same time, more consideration should be given to investment promotion, enterprise wastewater supervision, and wastewater treatment fees in the park.